Physiochemical and electrical activities of nano copper oxides synthesised via hydrothermal method utilising natural reduction agents for solar cell application - Rajabi A.; Boon Kar Y.; Doroody C.; Sieh Kiong T.; Arzaee N.A.; Mohamad Noh M.F.; Beygisangchin M.; Ghotbi M.Y.; Alam M.N.E.; Venu H.; Soudagar M.E.M.; Asim N.; et al. (Walter de Gruyter GmbH, 2025)
The aim of this study is to explore the potential compatibility of copper oxide nano-powders synthesised via hydrothermal method for solar cell applications by triggering a reaction between copper acetate and various reducing agents derived from natural resources, including Arabic gum, molasses, starch, and vinegar. X-ray diffraction analysis revealed the crystalline phases of the synthesised materials, indicating the successful synthesis of copper oxide material, which was confirmed by identifying patterns that matched specific copper oxide phases. Fourier transform infrared spectroscopy was employed to analyse the molecular vibrations and chemical compounds present in the reducing agents. The reducing properties of the selected materials and their capacity to convert copper acetate into copper oxide were validated. Field-emission microscopy and transmission electron microscopy analyses of the synthesised copper oxide nanoparticles (NPs) revealed variations in particle size and morphology. These variations were dependent on the particular reducing agent utilised during synthesis. Moreover, the carrier concentration, mobility, and resistivity were evaluated as the electrical properties of the spin-coated copper oxide thin films. Hall effect analysis determined that the choice of reducing agent significantly influenced the carrier concentration (n) and mobility (?) of the films. Remarkably, nano copper oxide films synthesised using starch exhibited irregular spherical grains with porous surfaces. Starch-synthesised samples showed the highest conductivity of n = 1.2 ? 1019 cm-3 when compared with those synthesised with other reducing agents. This suggests that the porous surfaces in the starch-synthesised films may have contributed to their enhanced conductivity compared to films synthesised with alternative reducing agents. In summary, the findings emphasised the influence of the reducing agent on the size, morphology, and electrical conductivity of the copper oxide NPs. ? 2024 the author(s), published by De Gruyter.